2002
DOI: 10.1074/jbc.m208408200
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA-dependent Protein Kinase (pkr) Is Essential for Thermotolerance, Accumulation of HSP70, and Stabilization of ARE-containing HSP70 mRNA during Stress

Abstract: We have investigated the role of the double-stranded RNA-dependent protein kinase gene (pkr) in the regulation of the heat shock response. We show that the pkr gene is essential for efficient activation of the heat shock response and that pkr disruption profoundly inhibits heat shock protein 70 (HSP70) synthesis and blocks the development of thermotolerance. Despite these profound effects, pkr disruption did not markedly affect the activation of heat shock factor 1 by heat and did not reduce the rate of transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…Alfieri et al reported that the stability of mouse hsp70 mRNA can be altered by hypertonicity, and Zhao et al showed that the cis-acting A + U rich elements (ARE) in the 3'-untranslated region (UTR) of hsp70.1 controls the mRNA stability (Alfieri et al, 2002;Zhao et al, 2002). We found that human hsp70-2 mRNA had two AUUUA sequences in its 3' UTR.…”
Section: Discussionmentioning
confidence: 69%
“…Alfieri et al reported that the stability of mouse hsp70 mRNA can be altered by hypertonicity, and Zhao et al showed that the cis-acting A + U rich elements (ARE) in the 3'-untranslated region (UTR) of hsp70.1 controls the mRNA stability (Alfieri et al, 2002;Zhao et al, 2002). We found that human hsp70-2 mRNA had two AUUUA sequences in its 3' UTR.…”
Section: Discussionmentioning
confidence: 69%
“…To test this possibility, we sought a means of inhibiting the synthesis of endogenous heat shock proteins. It has been shown previously (51) that 2-aminopurine inhibits the synthesis of Hsp70, a finding in agreement with the fact that one of the kinases inhibited by 2-aminopurine, PKR, is required for the heat shock response (52,53). Therefore, we tested the effect of 2-aminopurine.…”
Section: Shsps Protect Cap-dependent Translation After Heat Shockmentioning
confidence: 76%
“…The nature of the cellular damage sensors is still unclear, but one recently elucidated mechanism involves the activation of the double-stranded RNA-activated kinase through activation of RAX/PACT (56,57). In the absence of double-stranded RNAactivated kinase, Hsp70 is not induced (53). Hsp70 induction is also blocked by 2-aminopurine (Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription decays rapidly after initiation, while HSF continues to bind to HSE for several hours after transcription is ceased 18,19 . HSP mRNA is then observed within 1 hr of activation and is maintained at these high levels for up to 24 hr due to enhanced stabilization after stress 20 . After acute stress, HSP protein expression is delayed due to initial translational inhibition but Hsp70, Hsp90 and Hsp110 are observed by 2-6 hr after a 43°C heat shock and can persist in cells for up to 100 hr 21 ( Figure 1).…”
Section: Nih Public Accessmentioning
confidence: 99%